Real options and foreign affiliate divestments: A portfolio perspective - Belderbos, René; Zou, Jianglei (Journal of International Business Studies, 2009)
This paper develops a real options portfolio perspective on foreign affiliate divestments. Affiliates are less likely to be divested in response to adverse environmental change if they represent growth or switch option value to the multinational firm under conditions of macroeconomic uncertainty. However, the affiliate is partially redundant to the option value of the multinational firm's affiliate portfolio if the affiliate shares the manufacturing platform role in the host country with other affiliates, or if macroeconomic conditions of the host country are highly correlated with those of other countries in which the multinational firm operates affiliates. We find strong support for these arguments in tests on a comprehensive sample of 1078 Asian manufacturing affiliates of Japanese electronics multinationals.